Pengaruh Model Problem Based Learning terhadap Hasil Belajar Siswa pada Materi Statistika di Kelas V SD Negeri 3 Peukan Pidie - Fauzi Ali; M. Yamin; Asharaina Asharaina (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2022)
Problem Based Learning Model is a learning model by focusing student with authentic problem so that student can construct their own mind, to grow and innovate higher skills, to make them believe in themselves. The aim of this research is to know the influence of Problem Based Learning Model toward the student achievement at statistical matery at grade V SD Negeri 3 Peukan Pidie. This research used quantitative approach and experiment by using  pre-experimental designs (non-designs) and one shot case study. Sample in this research consist of 33 students, those are 20 male and 13 female. Collecting data by using essay test. Data analysis to prove hypothesis by using t-test. From data analysis and proving hypothesis t-count = 8,12 at significant grade α = 0,05 and dk = n – 1 = 33 – 1 = 32, so distribution list t1 -α (dk) = t1- 0,05(32) found t0.95(32) =1,697. Because t-count  ˃  t-table = 8,12 ˃ 1,697 H0 rejected and H1 received. It can be concluded that the significant influence of Problem Based Learning Model toward student  achievement  at statistical matery at grade V SD Negeri 3 Peukan Pidie.